2009
DOI: 10.1002/humu.20936
|View full text |Cite
|
Sign up to set email alerts
|

ClassifyingMLH1andMSH2variants using bioinformatic prediction, splicing assays, segregation, and tumor characteristics

Abstract: Reliable methods for predicting functional consequences of variants in disease genes would be beneficial in the clinical setting. This study was undertaken to predict, and confirm in vitro, splicing aberrations associated with mismatch repair (MMR) variants identified in familial colon cancer patients. Six programs were used to predict the effect of 13 MLH1 and 6 MSH2 gene variants on pre-mRNA splicing. mRNA from cycloheximide-treated lymphoblastoid cell lines of variant carriers was screened for splicing aber… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
66
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 61 publications
(70 citation statements)
references
References 49 publications
4
66
0
Order By: Relevance
“…Instead, for MMR genes, there are not well-established models or well-characterized features 42 so that, at the time of writing, a very few groups have attempted to classify MMR UVs with the Bayesian likelihood method. The study by Arnold et al 24 investigated several variants, three of which are in common with our data (MLH1 c.307-29CϾA, c.1039-8 TϾA and MSH2 p.Gly322Asp): only c.307-29CϾA was analyzed by a similar comprehensive approach and assigned to class 3, as it is in our study.…”
Section: Discussionsupporting
confidence: 65%
See 2 more Smart Citations
“…Instead, for MMR genes, there are not well-established models or well-characterized features 42 so that, at the time of writing, a very few groups have attempted to classify MMR UVs with the Bayesian likelihood method. The study by Arnold et al 24 investigated several variants, three of which are in common with our data (MLH1 c.307-29CϾA, c.1039-8 TϾA and MSH2 p.Gly322Asp): only c.307-29CϾA was analyzed by a similar comprehensive approach and assigned to class 3, as it is in our study.…”
Section: Discussionsupporting
confidence: 65%
“…Moreover, three of the class 1 or 2 UVs (MSH2 p.Gly322Asp, MLH1 p.Ser406Asn and p.Val716Met) were classified as benign in a structured assessment study on MMR ambiguous mutations by Barnetson et al 34 MSH2 p.Gly322Asp and MLH1 c.1039-8TϾA were also considered by Arnold et al, 24 but not studied further, because they were found at polymorphic frequency in unaffected controls. This points to the potential value of our classification scheme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An intronic variant, c.1668-1 G > A, found in a heterozygous individual in 2KJPN, may cause exon skipping and is considered to be pathogenic [40]. Another missense variant, p.Arg687Trp, found in a heterozygous individual, was previously reported in two Japanese families with LS [41].…”
Section: Lynch Syndrome Genesmentioning
confidence: 94%
“…For genes with a large diagnostic interest, for example, breast and colon cancer, a committee of experts can be established that regularly meets to discuss the topic and give their expert opinion on the associated functional consequences and list this in the database. This committee can use software tools specifically built for the gene of interest to evaluate the potential consequences of each variant [Arnold et al, 2009;Jordan et al, 2011;Tavtigian et al, 2008].…”
Section: Answering Questionsmentioning
confidence: 99%